Una revisión de los efectos hidrológicos y erosivos del abandono de tierras en España - García-Ruiz, José María; Lana-Renault, Noemí (Geographicalia, 2014)
The hydrological and geomorphic effects of land abandonment in Spain are reviewed. The complexity of the evolution depends on the climatic features, soil characteristics, type of fields and land uses after the abandonment. In general, a decrease in discharge and soil erosion has been observed in mountain areas, though the terraced hillslopes can undergo an increase in soil erosion due to small mass movements and the reorganization of the drainage network. In semi-arid environments an increase in runoff generation and soil erosion has been detected owing the greater difficulties for plant colonization.